Tailoring Polymersome Bilayer Permeability Improves Enhanced Permeability and Retention Effect for Bioimaging - Lai, Mei-Hsiu; Lee, Sangmin; Smith, Cartney E.; Kim, Kwangmeyung; Kong, Hyunjoon (American Chemical Society, 2014)
Self-assembled nanoparticles conjugated with various imaging contrast agents have been used for the detection and imaging of pathologic tissues. Inadvertently, these nanoparticles undergo fast, dilution-induced disintegration in circulation and quickly lose their capability to associate with and image the site of interest. To resolve this challenge, we hypothesize that decreasing the bilayer permeability of polymersomes can stabilize their structure, extend their lifetime in circulation, and hence improve the quality of bioimaging when the polymersome is coupled with an imaging probe. This hypothesis is examined by using poly(2-hydroxyethyl-co-octadecyl aspartamide), sequentially modified with methacrylate groups, to build model polymersomes. The bilayer permeability of the polymersome is decreased by increasing the packing density of the bilayer with methacrylate groups and is further decreased by inducing chemical cross-linking reactions between the methacrylate groups. The polymersome with decreased bilayer permeability demonstrates greater particle stability in physiological media and ultimately can better highlight tumors in mice over 2 days compared to those with higher bilayer permeability after labeling with a near-infrared (NIR) fluorescent probe. We envisage that the resulting nanoparticles will not only improve diagnosis but also further image-guided therapies.
Keywords: DRUG-DELIVERY; MACROMOLECULAR THERAPEUTICS; CANCER; NANOPARTICLES; COPOLYMERS; MEMBRANES; MICELLES; FLUORESCENCE; DIAGNOSIS; VESICLES